KONTRIBUSI HASIL HUTAN BUKAN KAYU KEMIRI (Aleurites moluccana) TERHADAP PENDAPATAN PETANI HUTAN KEMASYARAKATAN (HKm) TANGGA DESA SELENGEN KECAMATAN KAYANGAN KABUPATEN LOMBOK UTARA - Nihad Kartila; Andi Chairil Ichsan; Markum Markum (Jurnal Belantara, 2018)
This research was intended to find Contribution of Non-Timber Forest Products Candlenut (Aleurites Moluccana) to Farmer’s Income of Tangga, supporting and inhibiting factors, and income improvement strategy of business non-timber forest products candlenut. The research location in Tangga hamlet, Selengen Village, Kayangan District, North Lombok Regency, West Nusa Tenggara Province. This research used interview method with questionnaire tool to 36 respondents was carried on February 2018. The results showed Contribution of Non-Timber Forest Products Candlenut from region farmer community to farmer’s income was 63.2% /area of arable land or 63% /hectares, which support farmers to cultivate candlenut because it is very easy to develop, does not require intensive maintenance, harvest activities were very easy to do, technology tools used were traditional, and marketing process was easy to do. As well as barriers in the miscellaneous management of the lack of capital and the availability of limited tools in the processing of candlenut so that farmers can only sell candlenut in the form of logs that will reduce the income it receives, as well as the lack of knowledge and skills possessed by farmers. Income-generating strategy of the candlenut can be done with SO strategy (Strenght-Opportunity) that is developing the potency of candlenut with skill owned by farmer by utilizing simple tool technology. As well as increased cultivation and intensive candlenut intensive maintenance by utilizing the existing land area.